PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN KOMPETENSI PENGETAHUAN SISWA KELAS IV SDIT RAUDHATURRAHMAH PEKANBARU - Putri, Mirarian Shahra Putri Shahra; Marhadi, Hendri Marhadi Hendri; Alim, Jesi Alexander Alim Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is a classroom action research, which aims to increase knowledge of students class IV SDIT Raudhatturahmah Pekanbaru through Application of Problem-Based learning model (PBM)". Problem Based Learning Model is a series of teaching materials that begin delivery of a question which form the basis of the material delivered next. The learning model is based on the problem is a learning model that is based on a number of issues that require investigation authentic investigations requiring the completion of a real tangible, such as a natural phenomenon. Be implemented in September 2014. The subject of study is a student of class Pekanbaru which totaled 36 people. Based on the data obtained from teachers in Pekanbaru indicate that the minimum completeness criteria (KKM) which has been set at 75. Based on the results of the daily examination teachers give , students work completed in 23 people ( of this 63.9 % ) while the students who did not complete 13 people ( 36,1 % ) of 36 the number of students consisting of 14 women and 20 men. With an average of this 63.9 Technical analysis of the data that researchers use to measure the results of student learning through absorption obtained from the first daily test on the first cycle, the second daily test on the second cycle, seen from the base score with an average of 63.9 % increase in the first cycle with an average of 76.88 second cycle with an average of 89.05. So the increase of the base score is 66.6% siklus I of the basic score is 91.6% siklus II. In addition, the observation sheet presented are also conducted to observe the activities of teachers and students during the learning takes place, by filling in the fields of observation sheet that has been provided which is used to collect data on the activities of teachers and students of class IV activity SDIT Raudhatturahmah Pekanbaru. Percentage of teacher activity cycle I first meeting is 50% and 60% meeting II is the second cycle 1 meeting is 70% and the second meeting is 90% and the percentage of student learning activities in the first cycle is 50% meeting 1 and 2 meetings is 70%, the cycle second meeting of 1 was 75% and the second meeting is 95%. From the above results it is known that the application of problem based learning model can improve the knowledge of fourth grade students SDIT Raudhatturahmah Pekanbaru2014/2015.Keywords : Knowledge